Morphology, Ultrastructure and Possible Functions of Antennal Sensilla of Sitodiplosis mosellana Géhin (Diptera: Cecidomyiidae). Issue 1 (25th August 2016) - Wang, Yue; Li, Dan; Liu, Yang; Li, Xue-Jiao; Cheng, Wei-Ning; Zhu-Salzman, Keyan
Abstract: To better understand the olfactory receptive mechanisms involved in host selection and courtship behavior of Sitodiplosis mosellana (Diptera: Cecidomyiidae), one of the most important pests of wheat, scanning and transmission electron microscopy were used to examine the external morphology and ultrastructure of the antennal sensilla. The moniliform antennae exhibit obvious sexual dimorphism: antennae of the males are markedly longer than those of the females. Furthermore, each male flagellomere consists of two globular nodes, whereas each female flagellomere is cylindrical. Seven types of sensilla were identified in both sexes. Two types of s. chaetica have a lumen without dendrites and thick walls, suggesting that they are mechanoreceptors. S. trichodea and s. circumfila are typical chemoreceptors, possessing thin multiporous walls encircling a lumen with multiple dendrites. There are significantly more s. trichodea in female than in male, which may be related to host plant localization. In contrast, male s. circumfila are highly elongated compared to those of females, perhaps for pheromone detection. Peg-shaped s. coeloconica are innervated with unbranched dendrites extending from the base to the distal tip. Type 1 s. coeloconica, which have deep longitudinal grooves and finger-like projections on the surface, may serve as olfactory or humidity receptors, whereas type 2 s. coeloconica, smooth with a terminal pore, may be contact chemoreceptors. Also, this is the first report of Böhm' bristles at proximal scape on antennae of Cecidomyiid species potentially functioning as mechanoreceptors.